Kenya Discussion of 2023 Global Food Policy Report - CGIAR Initiative on National Policies and Strategies (CGIAR System Organization, 2023)
The International Food Policy Research Institute (IFPRI) is organizing a hybrid launch event for its 2023 Global Food Policy Report in Nairobi, Kenya, in collaboration with University of Nairobi and as part of the CGIAR Initiative on National Policies and Strategies (NPS) seminar series on May 19, 2023, at 2.00pm. The 2023 Global Food Policy Report, IFPRI’s flagship report, provides a broad set of evidence-based recommendations for better predicting and preparing for crises, addressing crises when they occur and building equity and resilience of food systems. The recent overlapping, complex shocks to food systems, including the COVID-19 pandemic, higher food prices, conflicts, and natural disasters have increased the risk of food insecurity, hunger, and malnutrition, thus disrupting livelihoods, increasing poverty, and further diminishing prospects for the world’s most vulnerable people. As crises become more frequent, complex, and prolonged, the report calls for reconsideration of food crisis responses, and building more long-term response solutions guided by solid evidence on the impacts of policies, programming, tools, and governance approaches. There is an urgent need for renewed and broader efforts to prevent, mitigate, and recover from crises in ways that build food system resilience, protect the livelihoods of women and marginal groups, ensure their inclusion in crisis response, and address the impacts of conflict and migration. The Kenya discussion of IFPRI’s 2023 GFPR will present key findings and recommendations of the report at global and regional levels. A distinguished set of discussants will then present their reflections on the report and provide insights on crisis response and resilience building in Kenya.